2019
DOI: 10.1111/cpr.12691
|View full text |Cite
|
Sign up to set email alerts
|

CB1 enhanced the osteo/dentinogenic differentiation ability of periodontal ligament stem cells via p38 MAPK and JNK in an inflammatory environment

Abstract: Objectives Periodontitis is an inflammatory immune disease that causes periodontal tissue loss. Inflammatory immunity and bone metabolism are closely related to periodontitis. The cannabinoid receptor I (CB1) is an important constituent of the endocannabinoid system and participates in bone metabolism and inflammation tissue healing. It is unclear whether CB1 affects the mesenchymal stem cell (MSC) function involved in periodontal tissue regeneration. In this study, we revealed the role and mechanism of CB1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 62 publications
3
57
0
Order By: Relevance
“…The effect of AEA was abolished by the simultaneous application of CB1 and CB2 inhibitors [19]. A recent study suggests that CB1 receptor might regulate osteogenic differentiation of periodontal ligament cells [20].…”
Section: Introductionmentioning
confidence: 93%
“…The effect of AEA was abolished by the simultaneous application of CB1 and CB2 inhibitors [19]. A recent study suggests that CB1 receptor might regulate osteogenic differentiation of periodontal ligament cells [20].…”
Section: Introductionmentioning
confidence: 93%
“…differentiation ability of periodontal ligament stem cells via p38 MAPK and JNK in an inflammatory environment (Yan et al, 2019). Bone morphogenetic protein-9 induces PDLSCs osteogenic differentiation through the ERK and p38 signal pathways (Ye et al, 2014).…”
Section: A B Cmentioning
confidence: 99%
“…and osteogenic differentiation of PDLSCs. He et al [74] and Yan et al [75] found that hypoxia and cannabinoid receptor I (CB1) could alter the activity of PDLSCs through the p38/MAPK pathway. Meanwhile, the PI3K-AKT-mTOR pathway [76] and NF-κB axis [77] are also involved in the modula-tion of PDLSCs.…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…It has been reported that antidifferentiation noncoding RNA (ANCR) [ 70 ], long noncoding RNAs (lncRNAs) [ 71 ], and microRNA-182 and microRNA-214 [ 72 , 73 ] regulate the proliferation and osteogenic differentiation of PDLSCs. He et al [ 74 ] and Yan et al [ 75 ] found that hypoxia and cannabinoid receptor I (CB1) could alter the activity of PDLSCs through the p38/MAPK pathway. Meanwhile, the PI3K-AKT-mTOR pathway [ 76 ] and NF- κ B axis [ 77 ] are also involved in the modulation of PDLSCs.…”
Section: Periodontiummentioning
confidence: 99%